Implementation of field-oriented control (FOC) for induction motor by using field-programmable gate array (FPGA) - Da, Zijian (2016)
In today’s power system, electric motor is main power system equipment and it is widely used in industrial, agricultural and many aspects in social life. The control of DC motor is simple and the control of AC motor is difficult. But AC motor, especially squirrel-cage induction motor, has the advantage of simple structure, sturdy, durable and inexpensive. Because of the advantages of AC motor, field oriented control is produced to simulate the DC motor torque control law to three-phase AC motor. This project is to develop the field oriented control scheme for induction motor and permanent magnetic synchronous motor, and simulate the system to get the results. For this project, the dynamic model for induction motor and PMSM has been developed to adapt the need of field oriented control. Field oriented control simulation models need to be built. And the field oriented control characteristics of each motor can be concluded via the simulation of models. These characteristics can be used in real motor for future work.